Multi-trajectories in different domains of social supports and subjective motoric cognitive risk syndrome: a 16-year group-based multi-trajectory analysis - Hui-Min Chuang; Lin-Chieh Meng; Chih-Kuang Liang; Fei-Yuan Hsiao; Liang-Kung Chen (Elsevier, 2024)
Objective: The aim of this study was to examine the longitudinal relationships between the trajectories of distinct subtypes of various domains of social supports and risk of subjective motoric cognitive risk (MCR) syndrome. Design: Longitudinal cohort study. Setting and participants: 2,279 participants in the Taiwan Longitudinal Study on Aging (TLSA) between 1999 and 2011. Method: A group-based multi-trajectory modeling (GBMTM) was implemented to identify distinct trajectory subtypes within various social support domains, encompassing social networks, emotional support, instrumental support, as well as working and economic status. Logistic regression models were then utilized to evaluate the associations between these trajectory subtypes and the risk of subjective MCR. Results: Among 2,279 participants, GBMTM identified four distinct trajectory subtypes: ''low social support'' (n = 371), ''medium social support '' (n = 862), ''high social support'' (n = 292), and ''high social support with employment'' (n = 754). The incidence rates of subjective MCR for these groups were 9.4%, 9.0%, 4.1%, and 0.8%, respectively. After adjusting for age, sex, education level, and comorbidities, both "low social support" (adjusted odds ratio (aOR) 4.07, 95% CI [1.60-10.34]) and "medium social support" (aOR 3.10, 95% CI [1.26−7.66]) were significantly associated with an increased risk of subjective MCR compared to the ''high social support with employment'' group. Conclusions and implications: The current study demonstrates that social support significantly reduces the risk of subjective MCR, with lower support levels correlating to higher risk, necessitating further intervention studies to confirm the link between social support and risk of subjective MCR.